Comparison between the Comfort and Hartwig sedation scales in pediatric patients undergoing mechanical lung ventilation - Carvalho, Werther Brunow de; Silva, Paulo Sérgio Lucas da; Chiu, Seing Tsok Paulo; Fonseca, Marcelo Machado Cunio; Belli, Luiz Antônio (São Paulo Medical Journal, 1999)
CONTEXT: A high number of hospitalized children do not receive adequate sedation due to inadequate evaluation and use of such agents. With the increase in knowledge of sedation and analgesia in recent years, concern has also risen, such that it is now not acceptable that incorrect evaluations of the state of children's pain and anxiety are made. OBJECTIVE: A comparison between the Comfort and Hartwig sedation scales in pediatric patients undergoing mechanical lung ventilation. DESIGN: Prospective cohort study. SETTING: A pediatric intensive care unit with three beds at an urban teaching hospital. PATIENTS: Thirty simultaneous and independent observations were conducted by specialists on 18 patients studied. DIAGNOSTIC TEST: Comfort and Hartwig scales were applied, after 3 minutes of observation. MAIN MEASUREMENTS: Agreement rate (kappa). RESULTS: On the Comfort scale, the averages for adequately sedated, insufficiently sedated, and over-sedated were 20.28 (SD 2.78), 27.5 (SD 0.70), and 15.1 (SD 1.10), respectively, whereas on the Hartwig scale, the averages for adequately sedated, insufficiently sedated, and over-sedated were 16.35 (SD 0.77), 20.85 (SD 1.57), and 13.0 (SD 0.89), respectively. The observed agreement rate was 63% (p = 0.006) and the expected agreement rate was 44% with a Kappa coefficient of 0.345238 (z = 2.49). CONCLUSIONS: In our study there was no statistically significant difference whether the more complex Comfort scale was applied (8 physiological and behavioral parameters) or the less complex Hartwig scale (5 behavioral parameters) was applied to assess the sedation of mechanically ventilated pediatric patients.